The notion of Lego© Mindstorms as a powerful pedagogical tool: Scaffolding learners through computational thinking and computer programming - Chetty, Jacqui (The IIE, 2015)
This paper documents a study that was conducted with regard to the use of robotics as an innovative pedagogical tool for computer programming. The robotics in question relate to the Lego Mindstorms robots that were introduced as a means to develop further learners’ problem-solving skills and motivate learners to have fun while learning. Vygotsky’s philosophy regarding the Zone of Proximal Development supports the notion of Lego Mindstorms robots as a pedagogical tool. A mixed methods study was conducted and the aim of the project was twofold. Firstly, to determine whether robots reinforce fundamental computer programming concepts that were taught in the classroom environment. Secondly, to determine whether robots provide motivation and interest in computer programming. The issues regarding the pedagogical approach are discussed and feedback from learners is analysed. The results are positive and encouraging.
Keywords: Pedagogy; Computer Programming; Computational Thinking; Robotics